Impact of local content policy on job creation through firms' participation and backward linkages in Nigerian Oil Sector - Niran, Adedeji Abdulkabir (2016)
A common objective of many oil-rich countries, especially developing oil-dependent countries, is to maximise the economic benefit of naturally occurring extractive resources by using them for developing of local and national economies. By exploring their natural resources these countries seek primary benefits including local value creation (with particular reference to indigenous oil firms‟ participation), backward linkages development, as well as job creation for the local workforce in the industry. Government intervention in the oil sectors in through of regulatory policies was a strategy often used for obtaining maximum benefits from oil resources. One common utility of such policies is the local content policy (LC policy). The LC policy has potential and is used to create more entrepreneurial opportunities that favour indigenous oil service companies and the development of backward linkages (i.e. utilisation of local input materials) in the industry, eventually creating more jobs for the citizens. Accordingly, a majority of people can benefit from their country‟s national resources and more value can be created within the local economy. Nigeria is ranked among the most resource-rich developing countries in the world. It is rich in crude oil and natural gas; and its economy depends heavily on oil wealth. The activities in the Nigerian petroleum sector are impressive and play a significant role in improving the country‟s growth in gross domestic product (GDP). The contribution of oil and gas to the GDP was more than 40% in 2013. Recently, the receipts from oil exports in 2014 represented approximately 74.4% of the total national exports. Earnings from the petroleum sector in the first quarter of 2015 were about US$14.2 billion (NBS, 2015). However, despite the multiple of entrepreneurial activities associated with oil exploration and production, only part of that wealth appeared to be captured by local firms. Utilisation of locally manufactured goods and services is low in the industry. This might have resulted in the low level of employment opportunities created for the local workforce in the oil and natural gas industry. The Nigerian government recognised the need to support and motivate indigenous oil firms in order to generate more opportunities for local employment and revenue generation in the industry, as well as to promote utilisation of local goods and services. Connectivity of the industry to local economies is termed „backward linkages‟. In order to achieve local economy value targets, the government intervened in the oil sector by introducing the LC policy in 2001. This policy‟s primary goal is to increase indigenous oil firms‟ participation in the petroleum sector and develop backward linkages through more jobs could be created. This action considered a part of a strategy to create more employment opportunities for locals in the industry.Noticeably, in Nigeria, the extent to which the LC policy influenced firms‟ participation in the petroleum sector, and their tendency to develop backward linkages has not yet been adequately assessed. Although a few studies investigated how successful the LC policy was, not only were mixed results reported, but also researchers overlooked the extent to which the policy influenced job creation through firms‟ participation and backward linkages. This generated divided views in the literature about the impact of the policy. In addition, although infrastructure is assumed to aid LC policy efficacy, the correlation effect between the policy and infrastructure has not yet been adequately analysed. This correlation has often been entirely ignored in previous studies.Therefore, this study assesses the impact of the LC policy on job creation through firms‟ participation and backward linkages in the Nigerian oil sector and evaluates the confounding effect of infrastructure on these variables. Survey data were obtained and analysed using Structural Equation Modelling (SEM). Since the relationships hypothesised between the variables in this study are theory-driven, the application of SEM, which is a theory testing method, is deemed appropriate for this study. SEM was applied not only to assess the reliability and validity of the variables, but also to examine the multiple, interrelated dependence relationships among them. Construct validity and discriminant validity of the measurement model were obtained through the confurmatory factor analysis (CFA) approach. Thereafter, the direct relationships among the variables, as well as the mediating effect of indigenous oil firms‟ participation (IOFP) and backward linkages (LINK) on the relationship between LC policy and job creation (JOB) were examined. Additionally, the bootstrap method using AMOS software was applied to analyse the multiple-mediation effects in this study.The results obtained indicated that the LC policy positively and significantly influenced IOFP and LINK. The coefficients of 0.34 and 0.19 support the hypotheses that the LC policy has a positive relationship with IOFP and LINK, respectively. More interestingly, the relationship between IOFP and JOB, and between LINK and JOB were found to be statistically significant. However, no relationship was observed between IOFP and LINK. This provided the insight that local firms have not been proactive in encouraging the development of backward linkages. The correlation between the LC policy and infrastructure (INF) was found to be statistically significant, but not as a prerequisite for LC policy efficacy. Moreover, the direction of INF on IOFP was found to be statistically significant, but the effect on LINK was insignificant. Further, IOFP and LINK in a multiple model were found to mediate the relationship between the LC policy and JOB. This indicated that IOFP and LINK jointly transmit the effect from LC policy to JOB. However, it was found that the effect through the three-path model operates more than the two-path model. This indicated that more jobs could be created for local labourers in the Nigerian oil sector with the effective impact of the LC policy on enhancing both local firms‟ participation and backward linkages. Based on the findings in the study, it is proved that the LC policy influenced indigenous firms‟ participation and the development of backward linkages in the Nigerian oil sector. However, considered as a set, the level of local content development in the sector is lower than the expected target. By implication, if substantial local value-addition is to be achieved, to spin-off sustainable economic and social development through the oil sector, the efficacy of the LC policy needs to be closely monitored.